Stem cell factor and cKIT modulate endothelial glycolysis in hypoxia - Jeong, Hayoung; Kim, Ryul I.; Koo, Hyunwoo; Choi, Yang Hee; Kim, Minju; Roh, Hyejin; Park, Sang Gyu; Sung, Jong Hyuk; Kim, Koung Li; Suh, Wonhee (Cardiovascular Research, 2024)
Aims: In hypoxia, endothelial cells (ECs) proliferate, migrate, and form new vasculature in a process called angiogenesis. Recent studies have suggested that ECs rely on glycolysis to meet metabolic needs for angiogenesis in ischaemic tissues, and several studies have investigated the molecular mechanisms integrating angiogenesis and endothelial metabolism. Here, we investigated the role of stem cell factor (SCF) and its receptor, cKIT, in regulating endothelial glycolysis during hypoxia-driven angiogenesis. Methods and results: SCF and cKIT signalling increased the glucose uptake, lactate production, and glycolysis in human ECs under hypoxia. Mechanistically, SCF and cKIT signalling enhanced the expression of genes encoding glucose transporter 1 (GLUT1) and glycolytic enzymes via Akt- and ERK1/2-dependent increased translation of hypoxia inducible factor 1A (HIF1A). In hypoxic conditions, reduction of glycolysis and HIF-1α expression using chemical inhibitors significantly reduced the SCF-induced in vitro angiogenesis in human ECs. Compared with normal mice, mice with oxygen-induced retinopathy (OIR), characterized by ischaemia-driven pathological retinal neovascularization, displayed increased levels of SCF, cKIT, HIF-1α, GLUT1, and glycolytic enzymes in the retina. Moreover, cKIT-positive neovessels in the retina of mice with OIR showed elevated expression of GLUT1 and glycolytic enzymes. Further, blocking SCF and cKIT signalling using anti-SCF neutralizing IgG and cKIT mutant mice significantly reduced the expression of HIF-1α, GLUT1, and glycolytic enzymes and decreased the pathological neovascularization in the retina of mice with OIR. Conclusion: We demonstrated that SCF and cKIT signalling regulate angiogenesis by controlling endothelial glycolysis in hypoxia and elucidated the SCF/cKIT/HIF-1α axis as a novel metabolic regulation pathway during hypoxia-driven pathological angiogenesis.
Keywords: Animals; Cell Hypoxia; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Glucose; Glucose Transporter Type 1; Glycolysis; Human Umbilical Vein Endothelial Cells; Humans; Hypoxia-Inducible Factor 1, alpha Subunit; Mice; Mice, Inbred C57BL; Neovascularization, Physiologic; Proto-Oncogene Proteins c-kit; Retinal Neovascularization; Signal Transduction; Stem Cell Factor; Angiogenesis; cKIT; Endothelial cell; Glycolysis; Hypoxia inducible factor; Stem cell factor